The handbook for companioning the mourner : eleven essentials principles - Wolfelt, Alan (Companion Press, 2009)
Partly a counseling model and partly an explanation of true empathy, this handbook explores the ways companionship eases grief. For caretakers who work with grieving people or for friends and family just hoping to stay close, 11 tenets are outlined for mourner-led care. These simple rules call for understanding another person's pain, listening with the heart rather than the head, not filling up every minute with words, respecting confusion and disorder, and relying on curiosity rather than expertise.